MAPA DE AMPLIFICACION SISMICA DEL VALLE CENTRAL, COSTA RICA - Ramírez, R. (2011)
Seismic amplification consist of a modification of the seismic signal when it travels from rockto soil strata. This causes variations in the amplitude and the frequency content of the signal when it reachesthe surface. This effect tends to cause a variation in the intensity with a possible increase in damage to infra-structure. To evaluate the degree of seismical signal amplification hazard a combination of the followingmaps is used:- Surface geology- Earthquake generating sources- Peaks of registered intensities- Natural period of the soil- Maximum possible peak acceleration, velocity and displacementThe map presented allows the calculation of high, medium and low relative hazard in conjunction with otheringineering parameters. Finally, the hazard map is compared with the urban development map, where a coin-cidence between the areas of larger residential growth and the areas with higher level of hazard of seismicamplification is observed.